EXTRAÇÃO DE ÁCIDO FÍTICO DE FONTES ALTERNATIVAS, PURIFICAÇÃO,CARACTERIZAÇÃO E AVALIAÇÃO DO POTENCIAL QUELANTE E ANTIOXIDANTE - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2010)
The phytic acid, a component of naturally occurring seeds, has a high chelating potential and depends on the pH can interact with metal ions that act as cofactors of several enzymes,interfering with essential metabolic processes. Phytic acid has antioxidant functions due to the formation of iron chelates, by suppressing the oxidative reactions catalyzed by this metal,which implies in a pronounced antioxidant function in the preservation of seeds. The price of pure phytic acid is very high, thus, techniques for extraction and purification can be improved to obtain the phytic acid with high purity degree. The purpose of this study consisted in to extract the phytic acid from pumpkin, watermelon, melon and papaya seeds, purify and characterize it by means of analytical techniques, to evaluate their chelating ability against the metal ion Fe (III), and investigate their antioxidant potential for possible use as a safe additive in food industry. Phytic acid was extracted in acid middle and mild conditions. For purification, was used a weak anion exchange resin, free base, and phytic acid elution was performed with a solution of hydrochloric acid 0.70 mol L-1. The solutions obtained had a purity of about 34 % compared to phytic acid solutions commercially available, and pumpkin seeds showed the highest content of phytic acid, 2.6325 (± 0.1994) g/100 g, dry matter. The phosphorus content in the different samples was similar and close to the amount of phosphorus found in the standard through the analytical curve. The thin-layer chromatography revealed that the extraction and purification procedures did not release phosphate from phytic acid molecule, as the inositol hexaphosphate was the main component obtained from different seeds. The data obtained from infrared and potentiometric studies revealed that phytic acid samples showed purity degree relatively high. The spectroscopic studies on UV-Vis showed that the phytic acid-Fe (III) complex, dodecassodium salt, presented an absorption band relating on the electron transfer from ligand to metal. The spectra for the phytic acid-Fe (III) complexes, obtained from seeds were similar, with high values of binding energy, suggesting that the interaction between phytic acid and the metal ion was effective. The phytic acid acts as a secondary antioxidant, thus it has not responded to trials of FRAP and DPPH, however,as evidenced by UV-Vis studies, phytic acid has a pronounced antioxidant function in preserving food due to the formation of stable chelates with Fe (III).
Keywords: ácido fítico; extração; purificação; caracterização; potencial quelante e antioxidante; phytic acid; extraction; purification; characterization; antioxidant and chelating potential; CNPQ::CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS